Anti-aging flame-retardant composite material and preparation process thereof
By preparing an anti-aging flame-retardant composite material containing components such as a composite flame retardant and an antioxidant, the shortcomings of existing cable materials in anti-aging, flame retardancy and high temperature resistance are solved, and the material's high temperature resistance, high strength and dimensional stability are achieved.
Patent Information
- Application Number
- CN202511085296.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-09-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing cable materials have deficiencies in anti-aging, flame retardancy and high temperature resistance, and are unable to meet the requirements of high temperature resistance, high strength and dimensional stability.
An anti-aging and flame-retardant composite material is prepared by mixing a composite flame retardant, an antioxidant, a compatibilizer, rare earth, an epoxy resin, a nano-metal oxide and an electromagnetic shielding additive.
The high temperature resistance, aging resistance and crack resistance of composite materials for cables are improved, and the mechanical properties and flame retardant effect of the materials are enhanced.
Smart Images

Figure CN120665400A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to an anti-aging and flame-retardant composite material and a preparation process thereof. Background Art
[0002] Cable is a general term for items such as optical cables and electrical cables. They are widely used in control installations, connecting devices, and transmitting power, making them a common and indispensable part of everyday life. However, because cables carry electrical current, their installation requires extreme caution. Cables are categorized by structure as symmetrical, coaxial, and composite cables, and by function as field, underground, and submarine cables. Communication cables have a wide transmission bandwidth and are less susceptible to external interference, but are difficult to repair. They are used for transmitting telephone, telegraph, and data signals. High-frequency cables are used to transmit high-frequency signals and exhibit distributed capacitance and inductance. In recent years, with the rapid development of advanced manufacturing, demand has skyrocketed for materials, particularly in aerospace, military, nuclear power, automotive, electronics, communications, and machinery, for materials with high temperature resistance, high strength, high modulus, dimensional stability, lightweight, electrical insulation, wear resistance, self-lubrication, and sealing properties. Specialized engineering cables are particularly well-suited to meet these requirements. Their excellent mechanical properties, radiation resistance, corrosion resistance, and flame retardancy make them a suitable material for high-temperature applications. To reduce costs, large amounts of inorganic fillers are often added. However, the addition of fillers significantly reduces the material's wear resistance. Therefore, creating flexible, inexpensive, wear-resistant, and aging-resistant cable materials has great application value. For example, patent CN114085456 discloses a method for preparing ceiling antenna cable materials. The method uses polypropylene, vulcanized nitrile rubber, white oil, and nano-zinc oxide to create a flame-retardant cable material. However, the material exhibits poor crack resistance, aging resistance, and high-temperature resistance. Summary of the Invention
[0003] (1) Technical problems solved
[0004] In view of the deficiencies in the prior art, the present invention provides an anti-aging and flame-retardant composite material and a preparation process, which improves the high temperature resistance, anti-aging and crack resistance of the composite material for cables.
[0005] (2) Technical solution
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: an anti-aging and flame-retardant composite material, which includes the following components by weight: 10-20 parts of a composite flame retardant, 20-25 parts of an antioxidant, 3-6 parts of a compatibilizer, 20-25 parts of rare earth, 14-16 parts of an epoxy resin, 15-25 parts of a nano-metal oxide, and 30-50 parts of an electromagnetic shielding additive.
[0007] Preferably, the composite flame retardant is any one of an organic acid and metal oxide composite flame retardant, a phosphorus-based composite flame retardant, a nitrogen-based composite flame retardant, an organic acid salt and a polyurethane composite flame retardant; the antioxidant is at least one of sodium sulfite, dibutylphenol, sodium thiosulfate and tert-butylated hydroxyanisole; the compatibilizer is at least one of benzoic anhydride grafted polystyrene, acrylic copolymers and isocyanates.
[0008] Preferably, the rare earth is one or more of lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, holmium, erbium, thulium, ytterbium, and lutetium; the nano metal oxide is one of nano silicon dioxide, nano titanium dioxide, and nano graphite tube; the epoxy resin is bisphenol A epoxy resin, novolac epoxy resin, or dicyclopentadiene epoxy resin; and the electromagnetic shielding additive is silver-plated aluminum, nano aluminum hydroxide, or nickel polyester composite fiber.
[0009] Preferably, the preparation method of the benzoic anhydride grafted polystyrene is: 2-4g toluene and 3-6g polystyrene are added to a reactor containing benzoic anhydride and a catalyst under the protection of nitrogen, the reaction temperature is 20-25°C, the reaction time is 20-24h, and a crude product is obtained, and then evaporation and chromatography separation are performed to obtain the benzoic anhydride grafted polystyrene.
[0010] Preferably, the mass ratio of the polystyrene, benzoic anhydride and catalyst is 0.46-0.51:1:0.04-0.07.
[0011] Preferably, the preparation method of benzoic anhydride is: nitrogen is introduced into a reactor, and benzoic acid, methylsulfonyl chloride, and oxetane are added to the reactor in sequence, and then a mixture of triethylamine and oxetane is added dropwise to the reactor at 0-3°C, stirred for 1-2 hours, and after the reaction is completed, evaporated, washed, extracted, and dried to obtain benzoic anhydride.
[0012] Preferably, the mass ratio of the benzoic acid, methylsulfonyl chloride and oxetane is 1:0.5-0.7:0.2-0.3.
[0013] Preferably, the catalyst for preparing the benzoic anhydride grafted polystyrene is triphenylphosphine.
[0014] Preferably, the preparation process of the anti-aging and flame-retardant composite material is:
[0015] (1) adding a composite flame retardant, an antioxidant, a compatibilizer, rare earth, an epoxy resin, a nano metal oxide, and an electromagnetic shielding additive sequentially into a crucible resistance furnace for melting at a reaction temperature of 90-110° C. for 30-40 min to obtain a preliminary material;
[0016] (2) After the initial material is kept warm for 50-70 seconds, it is poured and then taken out and quickly placed in constant temperature distilled water to cool for 3-4 seconds. This cycle is repeated 800-1000 times. The material is taken out and cut by a cutting machine, and then ground and polished to obtain an anti-aging and flame-retardant composite material.
[0017] Preferably, the pouring method in (2) is: adding the smelted raw material into a sand mold on a frequency-adjustable table at 1200-1500° C., vibrating at a frequency of 10-30 Hz for 4-6 hours.
[0018] (3) Beneficial technical effects
[0019] The present invention obtains a preliminary material by mixing and reacting various weight components, and then casting and cooling the material after melting. The material is cut by a cutting machine, and then ground and polished to obtain an anti-aging and flame-retardant composite material. Benzoic anhydride grafted polystyrene serves as a compatibilizer to enhance the compatibility and interaction between organic weight components. A tight molecular chain cross-linking network is formed between benzoic anhydride, polystyrene and organic components. The obtained composite material for cables has good mechanical properties and is resistant to cracking and bending. Rare earth elements can remove most free radicals and their own valence will change while the structure will not change, so they can be long-lastingly resistant to oxidation and aging. The composite flame retardant reduces the heat dissipated by absorbing heat during the decomposition process and reduces the flame temperature. During the decomposition, non-combustible gas is generated to reduce the oxygen content and inhibit the chain reaction. When the flame retardant on the surface of the composite material for cables burns, a dense protective layer is formed to achieve the purpose of flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the reaction circuit for grafting benzoic anhydride onto polystyrene.
[0021] Figure 2 It is a reaction circuit for preparing benzoic anhydride.
[0022] Figure 3 It is a cross-sectional view of an anti-aging and flame-retardant composite material. DETAILED DESCRIPTION
[0023] Example 1
[0024] The anti-aging and flame-retardant composite material of this embodiment includes the following components by weight: 10 parts of composite flame retardant, 20 parts of antioxidant, 3 parts of compatibilizer, 20 parts of rare earth, 14 parts of epoxy resin, 15 parts of nano-metal oxide, and 30 parts of electromagnetic shielding additive.
[0025] The preparation method of benzoic anhydride grafted polystyrene is as follows: toluene and 0.92g polystyrene are added to a reactor containing 2g benzoic anhydride and 0.08g catalyst under the protection of nitrogen, the reaction temperature is 20°C, the reaction time is 20h, and a crude product is obtained, which is then evaporated and chromatographically separated to obtain benzoic anhydride grafted polystyrene.
[0026] The preparation method of benzoic anhydride is as follows: nitrogen is introduced into a reactor, and 2 g of benzoic acid, 0.3 g of methylsulfonyl chloride, and 0.4 g of oxetane are added to the reactor in sequence, and then a mixture of triethylamine and oxetane is added dropwise to the reactor at 0°C, stirred for 1 hour, and after the reaction is completed, evaporated, washed, extracted, and dried to obtain benzoic anhydride.
[0027] The preparation process of the above-mentioned anti-aging and flame-retardant composite material is as follows:
[0028] (1) Aluminum hydroxide composite flame retardant, sodium sulfite antioxidant, benzoic anhydride grafted polystyrene compatibilizer, neodymium, samarium rare earth, bisphenol A epoxy resin, nano-silicon dioxide, and aluminum-plated silver are sequentially added into a crucible resistance furnace for melting at a reaction temperature of 90° C. for 30 min to obtain a preliminary material;
[0029] (2) The initial material is kept warm for 50 seconds before pouring. The melted cable liquid is added to the sand mold of the frequency-adjustable table at 1200°C with a vibration frequency of 10 Hz. It is vibrated for 4 hours and then taken out and quickly placed in constant temperature distilled water to cool for 3 seconds. This cycle is repeated 800 times. The cutting machine is taken out and cut, and the material is ground and polished to obtain an anti-aging and flame-retardant composite material.
[0030] Example 2
[0031] The anti-aging and flame-retardant composite material of this embodiment includes the following components by weight: 20 parts of composite flame retardant, 25 parts of antioxidant, 6 parts of compatibilizer, 25 parts of rare earth, 16 parts of epoxy resin, 25 parts of nano-metal oxide, and 50 parts of electromagnetic shielding additive.
[0032] The preparation method of benzoic anhydride grafted polystyrene is as follows: toluene and 1.02g of polystyrene are added to a reactor containing 2g of benzoic anhydride and 0.14g of catalyst under the protection of nitrogen, the reaction temperature is 25°C, the reaction time is 24h, and a crude product is obtained, which is then evaporated and chromatographically separated to obtain benzoic anhydride grafted polystyrene.
[0033] The preparation method of benzoic anhydride is as follows: nitrogen is introduced into a reactor, and 2 g of benzoic acid, 0.34 g of methylsulfonyl chloride, and 0.6 g of oxetane are added to the reactor in sequence, and then a mixture of triethylamine and oxetane is added dropwise to the reactor at 3°C, stirred for 2 hours, and after the reaction is completed, evaporated, washed, extracted, and dried to obtain benzoic anhydride.
[0034] The preparation process of the above-mentioned anti-aging and flame-retardant composite material is as follows:
[0035] (1) adding a metal oxide composite flame retardant, a dibutylphenol antioxidant, a polyacrylic acid compatibilizer, lanthanum, cerium, praseodymium, a phenolic resin, nano-titanium dioxide, and nano-alumina into a crucible resistance furnace in sequence and smelting them at a reaction temperature of 110° C. for 40 minutes to obtain a preliminary material;
[0036] (2) The initial material is kept for 70 seconds before pouring, and the melted cable liquid is added to the sand mold of the frequency-adjustable table at 1500℃, with a vibration frequency of 30Hz. It is vibrated for 6 hours and then taken out and quickly placed in constant temperature distilled water to cool for 4 seconds. This cycle is repeated 1000 times, and the cutting machine is taken out to cut it, and it is ground and polished to obtain an anti-aging and flame-retardant composite material.
[0037] Example 3
[0038] The anti-aging and flame-retardant composite material of this embodiment includes the following components by weight: 15 parts of composite flame retardant, 22.5 parts of antioxidant, 4.5 parts of compatibilizer, 22.5 parts of rare earth, 15 parts of epoxy resin, 20 parts of nano-metal oxide, and 40 parts of electromagnetic shielding additive.
[0039] The preparation method of benzoic anhydride grafted polystyrene is as follows: toluene and 0.97g polystyrene are added to a reactor containing 2g benzoic anhydride and 0.11g catalyst under the protection of nitrogen, the reaction temperature is 22.5°C, the reaction time is 22h, and a crude product is obtained, which is then evaporated and chromatographically separated to obtain benzoic anhydride grafted polystyrene.
[0040] The preparation method of benzoic anhydride comprises: introducing nitrogen into a reactor, and sequentially adding 2 g of benzoic acid, 0.32 g of methylsulfonyl chloride, and 0.5 g of oxetane into the reactor, then dropwise adding a mixture of triethylamine and oxetane into the reactor at 0-3° C., stirring for 1-2 hours, and after completion of the reaction, evaporating, washing, extracting, and drying to obtain benzoic anhydride.
[0041] The preparation process of the above-mentioned anti-aging and flame-retardant composite material is as follows:
[0042] (1) adding a polyurethane composite flame retardant, a sodium thiosulfate antioxidant, an isocyanate compatibilizer, gadolinium, holmium, erbium, a dicyclopentadiene epoxy resin, nano-magnesium oxide, and a nickel polyester composite fiber into a crucible resistance furnace in sequence and melting them at a reaction temperature of 100° C. for 35 minutes to obtain a preliminary material;
[0043] (2) The initial material is kept warm for 60 seconds before pouring. The melted cable liquid is added to the sand mold of the frequency-adjustable table at 13.5°C with a vibration frequency of 20 Hz. It is vibrated for 5 hours and then taken out and quickly placed in constant temperature distilled water for cooling for 3.5 seconds. This cycle is repeated 900 times. The cutting machine is taken out and cut, and the material is ground and polished to obtain an anti-aging and flame-retardant composite material.
[0044] Example 4
[0045] The anti-aging and flame-retardant composite material of this embodiment includes the following components by weight: 10 parts of composite flame retardant, 20 parts of antioxidant, 3 parts of compatibilizer, 20 parts of rare earth, 14 parts of epoxy resin, 15 parts of nano-metal oxide, and 30 parts of electromagnetic shielding additive.
[0046] The preparation method of benzoic anhydride grafted polystyrene is as follows: toluene and 0.9g polystyrene are added to a reactor containing 2g benzoic anhydride and 0.11g catalyst under the protection of nitrogen, the reaction temperature is 22.5°C, the reaction time is 22h, and a crude product is obtained, which is then evaporated and chromatographically separated to obtain benzoic anhydride grafted polystyrene.
[0047] The preparation method of benzoic anhydride is as follows: nitrogen is introduced into a reactor, and 2 g of benzoic acid, 0.34 g of methylsulfonyl chloride, and 0.6 g of oxetane are added to the reactor in sequence, and then a mixture of triethylamine and oxetane is added dropwise to the reactor at 3°C, stirred for 2 hours, and after the reaction is completed, evaporated, washed, extracted, and dried to obtain benzoic anhydride.
[0048] The preparation process of the above-mentioned anti-aging and flame-retardant composite material is as follows:
[0049] (1) adding a metal oxide composite flame retardant, a dibutylphenol antioxidant, a polyacrylic acid compatibilizer, lanthanum, cerium, praseodymium, a phenolic resin, nano-titanium dioxide, and nano-alumina into a crucible resistance furnace in sequence and smelting them at a reaction temperature of 110° C. for 40 minutes to obtain a preliminary material;
[0050] (2) The initial material is kept warm for 60 seconds before pouring. The melted cable liquid is added to the sand mold of the frequency-adjustable table at 13.5°C with a vibration frequency of 20 Hz. It is vibrated for 5 hours and then taken out and quickly placed in constant temperature distilled water for cooling for 3.5 seconds. This cycle is repeated 900 times. The cutting machine is taken out and cut, and the material is ground and polished to obtain an anti-aging and flame-retardant composite material.
[0051] Comparative Example 1
[0052] The anti-aging and flame-retardant composite material of this embodiment includes the following components by weight: 15 parts of composite flame retardant, 22.5 parts of antioxidant, 4.5 parts of compatibilizer, 22.5 parts of rare earth, 15 parts of epoxy resin, 20 parts of nano-metal oxide, and 40 parts of electromagnetic shielding additive.
[0053] The preparation method of benzoic anhydride grafted polystyrene is as follows: toluene and 0.92g polystyrene are added to a reactor containing 2g benzoic anhydride and 0.08g catalyst under the protection of nitrogen, the reaction temperature is 20°C, the reaction time is 20h, and a crude product is obtained, which is then evaporated and chromatographically separated to obtain benzoic anhydride grafted polystyrene.
[0054] The preparation method of benzoic anhydride is as follows: nitrogen is introduced into a reactor, and 2 g of benzoic acid, 0.34 g of methylsulfonyl chloride, and 0.6 g of oxetane are added to the reactor in sequence, and then a mixture of triethylamine and oxetane is added dropwise to the reactor at 3°C, stirred for 2 hours, and after the reaction is completed, evaporated, washed, extracted, and dried to obtain benzoic anhydride.
[0055] The preparation process of the above-mentioned anti-aging and flame-retardant composite material is as follows:
[0056] (1) adding a metal oxide composite flame retardant, a dibutylphenol antioxidant, a polyacrylic acid compatibilizer, lanthanum, cerium, praseodymium, a phenolic resin, nano-titanium dioxide, and nano-alumina into a crucible resistance furnace in sequence and smelting them at a reaction temperature of 110° C. for 40 minutes to obtain a preliminary material;
[0057] (2) The initial material is kept warm for 50 seconds before pouring. The melted cable liquid is added to the sand mold of the frequency-adjustable table at 1200°C with a vibration frequency of 10 Hz. It is vibrated for 4 hours and then taken out and quickly placed in constant temperature distilled water to cool for 3 seconds. This cycle is repeated 800 times. The cutting machine is taken out and cut, and the material is ground and polished to obtain an anti-aging and flame-retardant composite material.
[0058] The tensile properties of cable materials are measured in accordance with GB / T 1040.1-2018 using an electronic universal testing machine at a tensile rate of 50 mm / min, with specimens measuring 10 cm long, 2 cm wide, and 5 cm high. The flexural strength is measured in accordance with GB / T 9341-2008 using an electronic universal testing machine at a test rate of 3 mm / min, with specimens measuring 8 cm long, 4 cm wide, and 4 cm high. The flame retardancy of cables is measured in accordance with GB2406-1993 using a combustion barrel to determine the oxygen index.
[0059]
[0060] The cable tensile strength and elongation at break of Example 1 are the highest, reaching 26.4 MPa and 14.9%, respectively. Example 3 has the highest flame retardancy, reaching 30%, and Example 4 has the highest bending strength, reaching 35.4 MPa.
[0061] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. An anti-aging and flame-retardant composite material, characterized by: The invention comprises the following components by weight: 10-20 parts of composite flame retardant, 20-25 parts of antioxidant, 3-6 parts of compatibilizer, 20-25 parts of rare earth, 14-16 parts of epoxy resin, 15-25 parts of nano metal oxide, and 30-50 parts of electromagnetic shielding additive.
2. The anti-aging and flame-retardant composite material according to claim 1, characterized in that: The composite flame retardant is any one of an organic acid and metal oxide composite flame retardant, a phosphorus-based composite flame retardant, a nitrogen-based composite flame retardant, an organic acid salt and a polyurethane composite flame retardant; the antioxidant is at least one of sodium sulfite, dibutylphenol, sodium thiosulfate and tert-butylated hydroxyanisole; the compatibilizer is at least one of benzoic anhydride grafted polystyrene, acrylic copolymer and isocyanate.
3. The anti-aging and flame-retardant composite material according to claim 1, characterized in that: The rare earth is one or more of lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, holmium, erbium, thulium, ytterbium, and lutetium; the nano metal oxide is one of nano silicon dioxide, nano titanium dioxide, and nano graphite tube; the epoxy resin is bisphenol A epoxy resin, novolac epoxy resin, and dicyclopentadiene epoxy resin; and the electromagnetic shielding additive is aluminum silver plating, nano aluminum hydroxide, and nickel polyester composite fiber.
4. The anti-aging and flame-retardant composite material according to claim 2, characterized in that: The preparation method of the benzoic anhydride grafted polystyrene comprises: adding toluene and polystyrene into a reactor containing benzoic anhydride and a catalyst under the protection of nitrogen, reacting at a temperature of 20-25° C. for 20-24 hours to obtain a crude product, and then performing evaporation and chromatographic separation to obtain the benzoic anhydride grafted polystyrene.
5. The anti-aging and flame-retardant composite material according to claim 4, characterized in that: The mass ratio of the polystyrene, benzoic anhydride and catalyst is 0.46-0.51:1:0.04-0.
07.
6. The anti-aging and flame-retardant composite material according to claim 4, characterized in that: The preparation method of benzoic anhydride comprises: introducing nitrogen into a reactor, and sequentially adding benzoic acid, methylsulfonyl chloride, and oxetane into the reactor; then dropwise adding a mixed solution of triethylamine and oxetane into the reactor at 0-3° C., stirring for 1-2 hours, and after the reaction is completed, evaporating, washing, extracting, and drying to obtain benzoic anhydride.
7. The anti-aging and flame-retardant composite material according to claim 6, characterized in that: The mass ratio of the benzoic acid, methylsulfonyl chloride and oxetane is 1:0.15-0.17:0.2-0.
3.
8. The anti-aging and flame-retardant composite material according to claim 4, characterized in that: The catalyst for preparing the benzoic anhydride grafted polystyrene is triphenylphosphine.
9. The process for preparing the anti-aging and flame-retardant composite material according to claim 1, characterized in that: The preparation process of the anti-aging and flame-retardant composite material is as follows: (1) adding a composite flame retardant, an antioxidant, a compatibilizer, rare earth, an epoxy resin, a nano metal oxide, and an electromagnetic shielding additive sequentially into a crucible resistance furnace for melting at a reaction temperature of 90-110° C. for 30-40 min to obtain a preliminary material; (2) After the initial material is kept warm for 50-70 seconds, it is poured and then taken out and quickly placed in constant temperature distilled water to cool for 3-4 seconds. This cycle is repeated 800-1000 times. The material is taken out and cut by a cutting machine, and then ground and polished to obtain an anti-aging and flame-retardant composite material.
10. The process for preparing the anti-aging and flame-retardant composite material according to claim 9, characterized in that: The pouring method in (2) is as follows: adding the smelted raw material into a sand mold on a frequency-adjustable table at 1200-1500° C., vibrating at a frequency of 10-30 Hz for 4-6 hours.